Stress Kerja dan Pengaruhnya Terhadap Prestasi Kerja Karyawan Bank Konvensional di Kota Padang - Yeni, Novida (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2009)
Information concerning dynamics of stress employees labour capacity and very needed as one of the development strategy effort an banking isntitute. How storey; level of stres work characteristic and employees any kind of wich is have potency to influence their stres in relating to client it is important to know by bank management party side. This research aim to kow relation/ link among/ between stres work with conventional bank employees labour capacity and also to identify any kind of factor which is very have potency to influence employees labour capacity at conventional bank. Analysis appliance the used is test of Chi-Square. Result of research of showing that do not there are ralation/ link which is signifikan among/ between stras work with employees labour capacity. Employees owning low stres show high labour capacity, anough, and employees owning high stres, remain to earn to show its high labour capacity. Become, here seen that job/ activity stres had by low employees, but showing its high labour capacity. Thoungh there are some factor becoming the source of cause of stres laike condition of outside organization and also in organization. but both the things very influenced by condition of individual or personal. DIfference of this individual in the end become natural someone determinant of stres or do not. Therefore, need that good stres in and also outside work laboured by as low as possible, so that/ to be most poeple can to facing him/ it without a hitch.